2015
DOI: 10.1007/s11442-015-1224-5
|View full text |Cite
|
Sign up to set email alerts
|

Competition of spatial service hinterlands between high-speed rail and air transport in China: Present and future trends

Abstract: Abstract:The rapid development of high-speed rail (HSR) and air transport in China has encouraged research on the spatial effects and safety of these two modes of transport, and on the competition between them. We report here an investigation of the effects of competition between HSR and air transport in China from a geographical perspective. The spatial service hinterlands for HSR and air transport accessible within one and two hours by road transport were investigated using a method based on a geographical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Thus, we applied the proportion of domestic tourism revenue and regional GDP (TOURISM) to represent the region's dependence on the tourism industry. HSR development brought competition in spatial service hinterlands between HSR and air transport (Wang et al, 2015). Newly launched HSR stations or changed HSR links might induce flight seasonality.…”
Section: Global Model and Variable Selectionmentioning
confidence: 99%
“…Thus, we applied the proportion of domestic tourism revenue and regional GDP (TOURISM) to represent the region's dependence on the tourism industry. HSR development brought competition in spatial service hinterlands between HSR and air transport (Wang et al, 2015). Newly launched HSR stations or changed HSR links might induce flight seasonality.…”
Section: Global Model and Variable Selectionmentioning
confidence: 99%
“…In doing so, we assess both the substitutability and complementarity effects that coexist in Spring's entry decisions, particularly when route distances are split based on the characteristics of Spring's business model. We also consider the presence of HSR at the endpoint(s) of a route, which is critical since the number of airports overlapping with HSR services has increased year by year [41,42].…”
Section: The Substitutability and Complementarity Between Hsr And Air...mentioning
confidence: 99%
“…Dobruszkes [13] pointed out that if HSTs (high-speed trains) are to compete successfully with airplane, a number of factors come into play, including travel time, frequencies, fares, airline hubs, geographical structures of urban regions, etc. Wang et al [14] showed that the operational performance of HSR trains is not only influenced by population densities and well-developed economies, but also by fares, frequency, travel distance, departure time and distance from airports/HSR station to the city centre.…”
Section: B Research On Operational Performancementioning
confidence: 99%